(untitled) (Fiep Bulletin - online, 2014)
Introduction: In the current design, nursing is part of a team that quest, while exercising their professionals, produce and apply empirical knowledge and theoretical methodology assumptions in health, to better target and base its action. Currently, the nursing professionals have been hard for the practice of care in a holistic view, aiming the appreciation of the man like total being both in the health field as when performing functions of teaching, research and extension, considering changes in the educational system. Driven by the educational issues in nursing, focusing on the educator agent, we has as goals identify the educational actions developed during the training supervised and how planned and developed these actions. Methodology: Study which was to central focused on the pedagogical(educational) practice of nurse during supervised training at University Hospital Onofre Lopes (HUOL) in Natal, conducted with a intentional sample of 22 nurses working as supervisors with the training of graduate students and average level of nursing, who answered a questionnaire structured. Results: Talking about on the local of the educational activities were predominant Wards (72.7%) and ICU (13.6%), with emphasis on the actions of report / notes (100.0%) of nursing notes (95.5%) , individual guidance (90.9%), transition from nasogastric tube and gall bladder (90.9%), vein puncture (90.9%) and make curative (86.4%). As for the planning of educational activities, 88.9% do planning the supervised, 92.6% makes assessment of the pupils’ need of, 86,7% outlines goal, 81.5% selects techniques and teaching methods, 42.9% selects resources teaching and 97.6% makes evaluation. The predominant frequency of the shares was educational daily (59.5%), with students from Aux. / Téc. Nursing (66.7%), using individual method (52.8%), technical demonstration (35.5%) and discussion (29.0%) and evaluation through the observation (35.7%) and oral question ( 30.4%). Conclusion: The surveyed mostly had a good educational performance in planning and development of educational activities during supervised training in the institution.